Whole-animal genome-wide RNAi screen identifies networks regulating male germline stem cells in Drosophila - Ying Liu (Nature Portfolio, 2016)
Both intrinsic and external signals regulate stem cell fate. Here, the authors perform a genome-wide RNAi screen to identify regulators of testis germline stem cells (GSC) in Drosophila, finding more than half of the genes were external regulators and heterochromatin/cytokinesis proteins mediated GSC fate.